Effect of Different Washing Cycles on the Quality of Pangasius hypophthalmus Surimi - Hassan, M. A.; Balange, A. K.; Senapati, S. R.; Martin Xavier, K. A. (Fishery Technology, 2017)
Pangasius is a fish with low cost and round the year availability, which can be an alternate raw material to regular marine fish species like pink perch and croaker. Yellow discolouration of meat is the most serious problem in marketing Pangasius as fillet. There is a need to develop an alternative ways of utilizing Pangasius and making surimi is one of the alternatives. Therefore attempts have been made in the present investigation to optimize the process of surimi preparation from Pangasius hypophthalmus. Effect of different washing cycles i.e., one, two, three and four washes with 1: 3 mince to water ratio on the quality of Pangasius surimi was investigated. It was found that among the different washing cycles, third and fourth washing cycles have resulted in the highest gel strength and lowest expressible moisture of Pangasius surimi as compared with control and other treatments. The sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) study revealed disappearance of myosin heavy chain (MHC) in the surimi gel obtained with third and fourth washing cycle indicating good cross linking. With increasing washing cycle whiteness of surimi was also improved. Sensory evaluation indicated highest overall acceptability for surimi obtained with third and fourth washing. However, the quality of surimi obtained from third and fourth washing was not different. Therefore, it can be concluded that three washing cycles with 1:3 mince: water ration can be optimum for making good quality surimi from Pangasius.